Communication in the third sector of social action: Local and participatory shift in the communicative performances - Blanco Morett, Álvaro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This publication addresses the challenges of the third sector communication, in the context of digitalization of social and productive processes, and social distancing caused by the health emergency of the Covid-19. The city is approached as a site of innovative communicative practices, aimed at raising awareness and information about eco-social challenges. This article presents a theoretical justification and a methodological research proposal to investigate participatory communication practices and the use of public spaces.